Plasticumwelt and umwelt diffraction: A new materialist ecosemiotics - Nicola Zengiaro (Sign Systems Studies)
The article explores the intricate relationship between plastic materials, semiotics and ecology, offering a novel perspective on the concept of umwelt in the context of pervasive plastic pollution. Drawing on semiotic, ecosemiotic and neo-materialist theories, it examines how plastic has become a ubiquitous presence in ecosystems, profoundly shaping the subjective worlds of organisms. The paper presents a theoretical analogy between the world of the spider and the production of its web on the one hand, and the human world and the production of plastic on the other hand, to show how the minds of animals extend along the production of their materials. Through the lens of material semiotics, the study elaborates the notion of ‘umwelt diffraction’, highlighting how synthetic materials disrupt the ecological dynamics and perception of organisms, forming the structure of a ‘plasticumwelt’. This reconceptualization underlines the urgent need for interdisciplinary approaches to address the challenges posed by plastic pollution. Ultimately, the article argues that plastic proliferation creates a toxic heritage, underlining the importance of sustainable practices to mitigate the harmful effects of plastic on biodiversity and ecosystem resilience.